A study to assess the clean hospital initiative and quality of health services using kayakalp tool in a first referral unit, of Khordha district of Odisha, India - Panda, Mayadhar; Nanda, Sikata (International Journal Of Community Medicine And Public Health, 2018)
Background: As a part of “Swachh Bharat Abhiyaan” campaign, the Ministry of Health and Family welfare, Govt. of India had launched “Kayakalp” in 2015, an initiative to promote cleanliness and enhance the quality of public health facilities. Our aim was to study the situational analysis of the health institution using Kayakalp tool; to assess the level of cleanliness, hygiene and infection control practices in the facility and to assess the status of Bio-medical waste management in the health care facility and to suggest remedial measures based on the study finding. Methods: It is a hospital based snapshot study done during a period of one year from April 2016 to March 2017. Kayakalp assessment tool was used for analysis. Results: The total scores for upkeep maintenance obtained in 2016-17 was 69 and for the year 2017-18 was 81. There was an increase of total score in the year 2017-18 and it was found to be statistically significant. On assessment in the year 2016-17, for BMW the total score obtained was 58 and in the year 2017-18 it was 81. There was a statistically significant increase in the scores (p=0.001) obtained in the year (2017-18). Conclusions: Improvements in Biomedical waste management can be made by increasing the knowledge, awareness and practices of the health care providers as well as the beneficiaries with regular periodic monitoring.